2014
DOI: 10.3390/antiox3020439
|View full text |Cite
|
Sign up to set email alerts
|

Avocado Seeds: Extraction Optimization and Possible Use as Antioxidant in Food

Abstract: Consumption of avocado (Persea americana Mill) has increased worldwide in recent years. Part of this food (skin and seed) is lost during processing. However, a high proportion of bioactive substances, such as polyphenols, remain in this residue. The primary objective of this study was to model the extraction of polyphenols from the avocado pits. In addition, a further objective was to use the extract obtained to evaluate the protective power against oxidation in food systems, as for instance oil in water emuls… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
38
0
7

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(45 citation statements)
references
References 47 publications
0
38
0
7
Order By: Relevance
“…Avocado seeds have relatively high antioxidant activity so that it can be considered as one of natural antioxidant sources (Malangngi, 2012). According to Arukwe et al (2012) and Gomez et al (2014), avocado seeds are rich in flavonoid, which shows radical capturing activity towards DPPH (Konsinska et al, 2012). Flavonoid plays the role as ROS through its reaction towards reactive compounds and free radicals which cause inactivity in damaged cell tissue.…”
mentioning
confidence: 99%
“…Avocado seeds have relatively high antioxidant activity so that it can be considered as one of natural antioxidant sources (Malangngi, 2012). According to Arukwe et al (2012) and Gomez et al (2014), avocado seeds are rich in flavonoid, which shows radical capturing activity towards DPPH (Konsinska et al, 2012). Flavonoid plays the role as ROS through its reaction towards reactive compounds and free radicals which cause inactivity in damaged cell tissue.…”
mentioning
confidence: 99%
“…(1) Avocado (Persea americana) Waste. e consumption of avocado is extensive globally [30]. e waste generated during processing of avocado for human consumption contains high concentrations of bioactive compounds such as polyphenols.…”
Section: Nutritious Dietary Resources Derived From Malus Domestica Wamentioning
confidence: 99%
“…The improvement in sperm quality and fertilizing ability indices in this study revealed the preservative effect of these extenders and could be attributed to the components of ASE that are essential for optimal survival of spermatozoa during vitrification. Avocados contain some minerals, lutein and antioxidants that are essential in cell functions (USDA, 2011;Dreher and Davenport, 2013;Gómez et al, 2014;Vedamurthy et al, 2015). Daramola James Olamitibo et al 370 Adverse effects of seminal oxidative stress on sperm quality have been evaluated using MDA concentration (Arabi and Seidaie, 2008;Piyali et al, 2009;Pasqualotto et al, 2000).…”
Section: Fertilizing Ability Indicesmentioning
confidence: 99%
“…The antioxidant property of avocado seed extract has recently been reported to remove 1,1-diphenyl,2picrylhydrazyl (Vedamurthy et al, 2015). A considerable percentage of polyphenols are also present in avocado (Gómez et al, 2014). Polyphenols are able to prevent cell damage caused by lipid peroxidation (Perumalla and Hettiarachchy, 2011).…”
Section: Fertilizing Ability Indicesmentioning
confidence: 99%
See 1 more Smart Citation